2012
DOI: 10.5617/nordina.423
|View full text |Cite
|
Sign up to set email alerts
|

University students’ ideas about data processing and data comparison in a physics laboratory course

Abstract: This study investigates undergraduate students' ability to use the ideas of measurement and uncertainty to process and compare experimental data. These ideas include not only knowing what it means to use an instrument to take a measurement, but also being able to apply that knowledge, including the ideas that make up uncertainty analysis, to every aspect of an experiment. A physics laboratory course for the Energy Systems Engineering programme at Uppsala University has been designed to focus on teaching studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 13 publications
3
17
0
2
Order By: Relevance
“…An alternative interpretation is that the RD probe is not effectively prompting many students to use reasoning aligned with the point-set paradigms. This interpretation is supported by findings at Uppsala University, where this probe was shown "not to distinguish among students who are experienced in the student laboratory at the sec-ondary and introductory university level [9]." The RD probe is the only PMQ probe that deals with a single data point (as opposed to sets of two or more measurements).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…An alternative interpretation is that the RD probe is not effectively prompting many students to use reasoning aligned with the point-set paradigms. This interpretation is supported by findings at Uppsala University, where this probe was shown "not to distinguish among students who are experienced in the student laboratory at the sec-ondary and introductory university level [9]." The RD probe is the only PMQ probe that deals with a single data point (as opposed to sets of two or more measurements).…”
Section: Resultsmentioning
confidence: 75%
“…The PMQ was first implemented at the University of Cape Town [5,6,8]. It has since been used at Uppsala University [9], the University of Maryland College Park [10,11], and North Carolina State University [12]. In all of these previous studies, the PMQ has been implemented in introductory lab courses, and has been used in an evaluative capacity for traditional or transformed labs.…”
Section: Introductionmentioning
confidence: 99%
“…Later work showed that while traditional courses improved procedural performance, only a small fraction of students exhibited a deeper conceptual understading after instruction [10]. The PMQ has also been used at Uppsala University, Sweden, showing that a lab course about measurement yielded mixed results in students' ability to appropriately use ideas about uncertainty [12]. In the United States, the PMQ has also been used at the University of Maryland College Park [13,14] and at North Carolina State University [15], both showing significant gains in understanding of measurement uncertainty after completion of research-based courses.…”
Section: Introductionmentioning
confidence: 99%
“…As pesquisas na área (KUNG; LINDER, 2006;MA-RINELLI;PACCA, 2006;LOVETT;SHAH, 2007;SILVA;SALES, 2010;LUB-BEN;BUFFLER, 2010;MUNIER;MERLE;BREHELIN, 2013, por exemplo) apontam que estudantes, em todos os níveis de ensino, possuem grandes dificuldades com relação aos conceitos e conhecimentos envolvidos no processo de medição e análise das medidas produzidas.…”
Section: Introductionunclassified